Poli Propilen (Pp) Sebagai Alternatif Untuk Kemasan AMDK Isi Ulang ( 5 Galon) - Wiwik Pudjiastuti; Samiha Syamsuddin (Jurnal Kimia dan Kemasan, 2001)
Packed drinking water is a commodity which is widely needed by the customer. One kind of the packaging used is reusable packaging with 5 (five) gallon capacity which is made from Poly Carbonat (PC) or Glass. Based on the technical, and safety reason, Poly Propylene (PP) can be used as an alternative for the reusable packaging of the drinking water.